Seeking of hotel room online purchase intention: case study Misteraladin.com - Ida Ayu Iswari Pidada; Ni Nyoman Triana Margareta (Institute of Computer Science (IOCS), 2024)
This research was conducted for determine the influence online customer review, price, and e-service quality on purchase intention hotel rooms on the OTA site Misteraladin.com. The research was conducted use descriptive quantitative analysis techniques and consisted of several initial hypotheses in the research. The population in this research were followers of the Misteraladin Instagram account use non-probability sampling techniques with the Purposive Sampling method. Based on this sampling technique, 100 samples of users of the Misteraladin Instagram account followers were determined as research respondents. The type of data that used is primary data using a questionnaire and utilizing multiple linear regression analysis techniques with IBM Statistics SPSS 26 software for determine the impact between the independent variables and the dependent variable. The results of this research show that online customer review and e-service quality have a positive and significant effect on purchase inten hotel rooms on the OTA Misteraladin.com site, while price does not have a significant positive effect on purchase intention hotel rooms on the OTA Misteraladin.com site